Penerapan Teknik Slashing dalam Pembuatan Ready To Wear Look Harajuku - Ariyana Damayanti; Endang Eka Setianingrum (Garina, 2024)
Beautifying the appearance of a garment requires modifications in dress. One way of beautifying clothing is fabric manupulation or fabric manipulation. The author chose the slashing technique, this technique is one of the fabric manipulation techniques by stacking several fabrics and then cutting one or several layers of the cloth pile so that it only makes the basic layer. The author compares many layers of fabric used. The goal is to know application of slahsing method creation in making ready to wear. The method that the author uses is the method of R&D and data analysis. The author made a comparison using 3 layers of material, 4 layers of material, and 5 layers of material. Comparisons of each slashing technique include materials, techniques, colors, and designs. The materials used to make the slashing technique are toyobo cotton fabric and drill fabric. The result of slashing 3 layers of material has a fabric thickness that is not too thick, the finished product is quite neat, and the color is suitable. Slashing 4 layers of material has a fairly thick fabric thickness, and the finished result is quite neat. Slashing 5 layers of material has a very thick thickness of fabric, and the finished result is not neat enough. Making ready to wear using a suitable slashing technique is 3 layers of fabric.